Analysis of Bureaucratic Performance in Improving the Quality of Services in the Education and Health Sector in Pasaman District - Rusta, Andri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
This study aims to analyze the performance of the bureaucracy in improving the quality of public services for the Pasaman Regency government in the education and health sectors. In the implementation of public services, Pasaman Regency is included in the category (yellow zone) in services with moderate compliance categories. In 2018 Pasaman Regency was in the Very High Ranking based on the EPPD Performance Evaluation and Performance of the Regency. Passover. In addition, based on the analysis of Macro Performance Indicator data, the performance of the Pasaman Regency government has experienced an increase in performance. This study used a qualitative approach with descriptive methods. This study aims to analyze and describe the performance of the bureaucracy in improving the service quality of the Pasaman District Government by conducting documentation studies and in-depth interviews. The results of the study showed that efforts to improve public services can be seen from the policy direction of the Pasaman Regency government through a Budget Policy which allocates more to social spending than personnel spending. Furthermore, as an effort to bureaucratic effectiveness, the Pasaman Regency Government streamlined the OPD so that the bureaucracy could run effectively. Then, service quality improvement was also carried out through UHC (Universal Health Coverages) policy innovations to provide the best health services to the community. As well as educational service innovations through a 12-year free education program until they graduate from high school or the equivalent for all student children in Pasaman Regency.